Secrets behind the gold medals: Why can China take a dominant position in the Paralympic Games? - Wang, Y.; Yang, A.; Kang, X. (Palaestra, 2020)
In 1984, China participated in the Paralympic Games for the first time. Over the past 3 decades, China has gradually grown into a "super power" that has won the majority of gold medals of the Paralympic Games from a "weak nation" in terms of elite sports for disabilities. Looking back at history, we should fully recognize the achievements. The study suggests that the reason why China takes a dominant position in the Paralympic Games lies in its 1) foundation of mass sport for IWD; 2) stable organizational management structure and the mission-oriented organization that prepares for the Paralympic Games in a targeted way; 3) strong competitive level supported by the training system, human resources, competitions, and venue facilities; 4) and incentives that encourage athletes to train hard for better results. The study also finds that currently China`s national team for IWD faces such problems as lack of long-term, systematic, and effective training, insufficient scientific research investment, low-tech equipment, the "Matthew Effect" in project development, and regional development imbalance.